2008
DOI: 10.1111/j.1365-2672.2008.03983.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross-transmission of clinicalEnterococcus faeciumin relation toespand antibiotic resistance

Abstract: Aims:  To investigate clonality among clinical Enterococcus faecium isolates and normal intestinal microflora isolates as well as cross‐transmission between patients in relation to the presence of the esp gene and antibiotic resistance. Methods and Results:  Blood‐culture isolates (n = 101) deriving from tertiary, secondary and primary hospitals were analysed. Antibiotic susceptibility was investigated. Polymerase chain reaction and pulsed‐field gel electrophoresis were used for detection of esp and genotyping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…In other studies, Enterococcusfaecalis was 85% (the most prevalent species), followed by E. faecium, which is the most common human pathogenic isolate (10,25,26). Enterococcus faecium has become increasingly prevalent in hospital-acquired infections (25).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In other studies, Enterococcusfaecalis was 85% (the most prevalent species), followed by E. faecium, which is the most common human pathogenic isolate (10,25,26). Enterococcus faecium has become increasingly prevalent in hospital-acquired infections (25).…”
Section: Discussionmentioning
confidence: 96%
“…Enterococcus faecium has become increasingly prevalent in hospital-acquired infections (25). All other enterococcal species together constitute less than 5% of enterococcal infections (10,25). In this study antimicrobial resistance pattern was indicated for enterococci with four antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Billström et al . ). The possibility for transmission is increased by the robust nature of the microorganism, resisting desiccation for weeks or even up to months (Howie et al .…”
Section: Introductionmentioning
confidence: 97%
“…2002), and recent studies indicate that Ent. faecium causing infections are often of non‐endogenous origin (Billström et al. 2008b; Lester et al.…”
Section: Introductionmentioning
confidence: 99%